Northern dimming and southern brightening in eastern China during the first decade of the 21st century - Li, Jingxin; Ma, Wenzhe; Yang, Su; Liu, Ge; Chen, Siyu; Ding, Minghu (Frontiers in Environmental Science, 2022)
Global solar radiation (GSR) reaching the Earth’s surface can directly alter the energy balance of the climate system. The potential influence of inhomogeneity issues on Chinese GSR records on dimming and brightening in China has been argued for years. In this study, we explored the temporal evolution and spatial distribution of the long-term trend of GSR in eastern China (EC) during 1961–2018 using a homogenized GSR dataset, which removed the artificial signals. Results demonstrate that EC experienced a significant dimming period from 1961 to 1999, a brightening period from 2010 until 2018 and a leveling-off period between them (2000–2010), which resulted from opposite trends of GSR in the northern (dimming) and southern (brightening) regions of EC. The reduction of cloud coverage after the dimming period (2000) induced an early coming brightening in the southern region of China between 2000 and 2010, while the increase in aerosols and the rapidly extending cloud fraction resulted in the continuing dimming in northern China